Financial development and the occurrence of banking crises - Mathonnat, Clément; Minea, Alexandru (Journal of Banking & Finance, 2018)
We perform an in-depth analysis of the effect of different dimensions of financial development on the occurrence of banking crises. Horse-race estimations carried out on a large dataset of 113 banking crises in 112 countries reveal that the growth of M3/GDP and the level of banks’ Credits/Deposits increase the occurrence of banking crises, while the growth and sometimes the volatility of the ratio of banks’ assets to the sum of banks’ and the Central Bank's assets decrease it. In addition, we do not find a significant effect of banks’ Credits/GDP. Finally, we unveil heterogeneities related to nonlinearities in the effect of financial development, the time span for the pre-crisis dynamics of financial development, and the level of economic development. Our results suggest that only some dimensions of financial development are significantly associated with the occurrence of banking crises.